2017
DOI: 10.1039/c7dt00128b
|View full text |Cite
|
Sign up to set email alerts
|

Comparative electronic structures of nitrogenase FeMoco and FeVco

Abstract: High-resolution X-ray spectroscopy provides insights into the electronic structural differences between the nitrogenase FeMoco and FeVco clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 70 publications
(91 reference statements)
10
124
0
2
Order By: Relevance
“…The blue arrows point toward the rising edge and white line onsets as well as indicate the MMCT feature. Adapted from ref (19), published by The Royal Society of Chemistry. See open access article: .…”
Section: Resultsmentioning
confidence: 99%
“…The blue arrows point toward the rising edge and white line onsets as well as indicate the MMCT feature. Adapted from ref (19), published by The Royal Society of Chemistry. See open access article: .…”
Section: Resultsmentioning
confidence: 99%
“…When the pre-edge features were modeled by pseudo-Voigt line shapes (excluding contributions from riding edge transitions), a comparison of the HERFD pre-edge area to the TFY pre-edge area shows that HERFD intensities are higher by a factor of ~1.3. The observed spectral features correspond to 1s to 3d transitions 3638 (at lowest energies, ~7110–7115 eV) with additional charge transfer contributions 35, 39 observed to higher energies (~7118 eV).…”
Section: Introductionmentioning
confidence: 92%
“…3235 The MMOH Q spectra are interpreted versus parallel studies on the open- and closed-core model compounds shown in Scheme 2. HERFD XAS is measured by scanning through the metal K-edge and measuring the resultant 2p-to-1s Kα-fluorescence using a high resolution Bragg optic.…”
Section: Introductionmentioning
confidence: 99%
“…Due to resolution limitations and the fact that homocitrate was severely truncated and approximated as a glycolate group in their study, the validity of this assignment was unclear. In previous studies 28,29,30,31,32 by one of us (RB) we have assigned the alkoxide group of the homocitrate as protonated but have not until now given a complete justification for this as the question of how well the protein environment is described surrounding the homocitrate remained unclear. The only exception to this is the 4ND8 crystal structure, recently published by Rees & Howard et al 85 which is a crystal structure solved under basic (pH 9.5) conditions, where the O-O distance is on average 2.77 Å as shown in Figure 6d.…”
Section: Protonation State Of Homocitratementioning
confidence: 99%
“…Recently Adamo 26 et al used QM/QM' calculations to propose new mechanisms and Ryde et al studied protonation states by QM/MM 27 . In previous articles by one of us (RB) we utilized large 225-atom cluster models in our studies of the spectroscopic properties of the FeMo cofactor 28,29,30,31,32 . Large cluster models become difficult to work with and require many constraints to keep the correct active site geometry and may not describe correctly the structural flexibility of the cofactor in the enzyme active site pocket.…”
Section: Introductionmentioning
confidence: 99%